Prototipo de gestión de eventos y alertas de dispositivos IoT en alarmas de seguridad en inmuebles (2022)
This project arises from the problem of insecurity in houses or shops that affects the calm and integrity of many of us, considering that currently these places have security systems that are not affordable for everyone. This is why this project has developed an affordable IoT prototype with open source hardware supported by a web platform which is developed in order to monitor and notify security companies or property owners through different media such as text messages (SMS) and email